Dataset on Effect of clonal integration on drought and waterlogging response in Urochloa humidicola - Cardoso Arango, Juan Andres; Mayorga Cobos, Mildred Julieth (2025)
Clonal integration enables the translocation of resources such as water, nutrients, and photosynthates among individual subunits of clonal plants, facilitating adaptation to diverse environmental conditions, including drought and waterlogging. Urochloa humidicola CIAT 679 (cv. Tully) exhibits strong adaptation to these abiotic stresses and propagates efficiently through stolons, maintaining clonal integration among shoots across different generations. The dataset corresponds to a study aimed to evaluate whether clonal integration is one of the strategies that confers tolerance to drought and waterlogging in CIAT 679. This dataset includes response data from donor and recipient ramets of Urochloa humidicola CIAT 679 (cv. Tully). Recipient ramets were exposed to six treatments, representing interactions between three stress conditions—drought, control (no stress), and waterlogging—under two clonal integration conditions: with and without integration. Each treatment had six replicates. The dataset comprises weekly measurements over three weeks for stomatal conductance, transpiration, and SPAD values. Additionally, final measurements include relative water content, aboveground biomass, root biomass, total biomass, root-to-shoot ratio, and non-structural carbohydrate content. This dataset provides valuable insights into the mechanisms by which Urochloa humidicola cv. Tully responds to drought and waterlogging stress. The findings may support plant breeding efforts by identifying traits associated with improved resilience in this species.